The impact of social support on the quality of sports participation among individuals with disabilities: the chain mediating effects of psychological capital and self-esteem - Peng, Jiahui; Cao, Li; Li, Feixuan; Zhou, Deqiao (Frontiers in Psychology, 2025)
BackgroundIndividuals with disabilities possess the right to equally participate in cultural, recreational, and sporting activities. Enhancing the quality of sports participation among this population is therefore of significant importance for promoting social equity. Grounded in Conservation of Resources Theory and the Social Cognitive Framework, this study focuses on the sequential transmission pathway involving psychological capital and self-esteem. It aims to elucidate the chain mediation mechanism through which social support influences the quality of sports participation among individuals with disabilities, thereby providing a theoretical foundation and practical targets for optimizing sports policies for this group.MethodsEmploying a stratified random sampling method, a cross-sectional questionnaire survey was conducted with 632 individuals with disabilities across 12 cities in 6 provinces spanning Eastern, Central, and Western China. Data collected were analyzed using SPSS for descriptive statistics, correlation analysis, and regression analysis. The bias-corrected bootstrap method (5,000 resamples) was utilized to test the chain mediating effects.Results(1) Social support significantly and positively predicted the quality of sports participation among individuals with disabilities (Total effect = 0.786, 95% CI [0.680, 0.891]), with the direct effect accounting for 49.87%. (2) Both psychological capital (β = 0.478) and self-esteem (β = 0.154) independently and positively predicted the quality of sports participation. (3) The total mediating effect of psychological capital and self-esteem was significant (Effect = 0.394, 95% CI [0.313, 0.484]), accounting for 50.13% of the total effect. Among the specific paths, “Social Support → Psychological Capital → Quality of Sports Participation” contributed the most (Effect = 0.294, Proportion = 37.41%). The chain path “Social Support → Psychological Capital → Self-Esteem → Quality of Sports Participation” was also significant (Effect = 0.025, Proportion = 3.18%).ConclusionSocial support not only directly enhances the quality of sports participation among individuals with disabilities but also facilitates a transformation from external empowerment to internal drive through the chain psychological mechanism of “Psychological Capital → Self-Esteem.” Theoretically, this study verifies the hierarchical progressive effect of positive psychological resources within the “Environment-Cognition-Behavior” pathway, deepening the psychological dynamic model of sports participation for individuals with disabilities. Practically, it suggests that improving participation quality requires the simultaneous construction of a multi-level social support network and the development of targeted integrated intervention programs focusing on psychological capital and self-esteem, to achieve a synergistic leap from participation “quantity” to experiential “quality.”